Physical and occupational therapist rehabilitation of lower extremity fractures in veterans with spinal cord injuries and disorders. (2nd January 2022) - Guihan, Marylou; Roddick, Kayla; Cervinka, Tomas; Ray, Cara; Sutton, Christopher; Carbone, Laura; Weaver, Frances M.
Abstract : Context/Objective: The risk of lower extremity (LE) fractures in persons with spinal cord injury or disorders (SCI/D) is double that of the able-bodied population. LE fractures are the most common fracture location in SCI/D. Physical therapists (PTs) and occupational therapists (OTs) play an important role in rehabilitating LE fractures in Veterans with SCI/D. This paper describes their role in assisting persons with SCI/D and LE fractures to return to previous function and levels of participation. Design: Cross-sectional semi-structured interviews were conducted by telephone. Setting: VA SCI centers Participants: Purposive sample of therapists (PTs and OTs) experienced in LE fracture rehabilitation in SCI/D Interventions: NA. Outcome Measures: Coding of responses used a data-driven thematic and deductive approach, dictated by a semi-structured interview guide addressing the entire treatment process. Results: Participants strongly advocated for early PT/OT involvement in post-fracture rehabilitation in order to recommend braces and devices to minimize skin breakdown, and needs for patient equipment, skills training and/or caregiver assistance resulting from post-fracture mobility changes. Seating specialists should be involved in post-fracture seating assessments in wheelchair users to address changes in alignment, deformities, limb length discrepancies and/or seating posture during and following fracture management. Conclusion: PTs and OTs are critical in rehabilitating LE fractures in persons with SCI/D and LE fractures, bringing expertise in patient function, ambulatory status, transfer strategies, mobility equipment, spasticity, lifestyle, and home and caregiver support. Involving them early in the rehabilitation process, along with orthopedic surgeons, physiatrists and other SCI clinicians can address the multiple and often unique issues that occur in managing fractures in this population.